Macroeconomic Volatilities and Long-Run Risks of Asset Prices - Zhou, Guofu; Zhu, Yingzi (Management Science, 2015)
In this paper, motivated by existing and growing evidence on multiple macroeconomic volatilities, we extend the long-run risks model by allowing both a long- and a short-run volatility components in the evolution of economic fundamentals. With this extension, the new model not only is consistent with the volatility literature that the stock market is driven by two, rather than one, volatility factors, but also provides significant improvements in fitting various patterns, such as the size of market risk premium, the level of interest rate, degree of dividend yield predictability, and the term structure of variance risk premiums, of both the equity and option data. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.1962. This paper was accepted by Jerome Detemple, finance.